A new genus of Isoperlinae (Plecoptera: Perlodidae) from Tibet, China - Huo, Qing-Bo; Du, Yu-Zhou (Zootaxa, 2021)
A new genus of family Perlodidae, Tibetisoperla Huo & Du, gen. nov. is described with one new species from Tibet, China. Male of the new genus is characterized by the divided tergum 10 with several large apical erect setae, highly reduced vesicle on sternum 8, and the sclerotized paraprocts with separate apical sclerite.